Ecological and Health Risk of Soils, Sediments, and Water Contamination - Hseu, Zeng-Yei (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The papers in this SI present valuable results in the topics of soils, sediments, and water contamination according to the consideration of ecological and health risk. They also point out open questions and possible avenues for future research. Biochar application can benefit both soil conservation and contamination, but further research should be conducted to investigate whether these positive effects can be extended to the field scale. Similar to biochar, scale-up design will be helpful for thin-layer capping in in situ sediments using mixed active amendments. Both physiochemical analysis and bioassays mutually supported the evaluation results of river water quality. However, we need better approaches and policies for management to prevent further contamination from the discharge of untreated industrial and domestic waste into this aquatic ecosystem. The use of microorganisms to eliminate antibiotics is a promising strategy, but future work should verify the biodegradation ability of antibiotic-degrading bacteria in wastewater treatment plants.